Fraud - Eva Ulfah Rahayu (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2014)
All Organizations, regardless of the type, form, scale of operations and activities are at risk of fraud. One of the factors that may lead to fraud is weak internal controls in the organization. Corporate governance applied in the company will have a positive impact on reducing the risk of fraud. In the application of corporate governance should be coupled with an effective management system and contains internal control that is run by people who are professional and responsible. Fraud in the company is management’s responsibility, but auditors also have the responsibility to find and disclose it by making a plan and audit work to get a reasonable assurance whether financial statement free from material misstatement, neither caused by error nor by irregularities. The evaluation of the organizational condition, the company’s structure and choices made are expected to help to disclose the motivation, opportunity and rationalization beyond the fraud of financial statement.